(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Rough surfaces are one of the most effective techniques to increase heat transfer. In this study, we have created rough surfaces in plain duct by (e/Dh = 0.043) with changing angle of rib 450 and 600. So we have developed an experimental setup with dimensions of the triangular duct base and height is 200mm and 350mm respectively. We had taken different readings at a constant flow rate and changing the temperature of the surface plate. From experimentation, we have found Reynolds number, Nusselt number and friction factor for three plates (plain, 450 and 600) and found 450 angle rib to have better results. Artificial roughness creates the turbulence to the flow which leads to increase the heat transfer between the air and the heated wall. Roughness is created in such a way that it breaks the laminar sub layer region i.e. near the wall. There is various method to provide artificial roughness on the absorber plate such as casting, forming, machining, blasting, welding ribs and/or fixing thin circular wires, etc. The easiest and cheapest way of providing artificial roughness on the underside of the absorber plate is sticking of ribs The scope for this study would focus all necessary activities for benchmarking the existing application with the current performance level and performance standards to be set for arriving at the objectives of the dissertation work.